The Importance of Romania's Public Health System In Meeting the Needs of People with Diabetes - Silvia Elena CRISTACHE; Narcisa Georgeta CIOBOTAR; Daniela SERBAN (Communications of International Proceedings, 2023)
The aim of this article was to understand the importance and role of the public health system in Romania in meeting the needs of people with diabetes. Research in the area of assessing the extent to which the types of support provided by the public health system meet patients' expectations is limited. A first objective of the research was to determine the predominant type of diabetes and the profile of the patient suffering from this type of diabetes. It was assumed that diabetes is a major concern of the public health system. The determination of the profile of the patient with type II diabetes aimed to identify the most susceptible type of person accessing the services offered by the public health system in order to mitigate the impact of the disease on their standard of living. It also aimed to determine the importance and role of the public health system from the perspective of the perception of people with type II diabetes with the determined profile. Thus, the objectives were to assess the efficiency and effectiveness of basic and related types of support provided by the public health system in relation to the extent to which people with type II diabetes make use of these types of support. The type of research chosen was quantitative research, based on qualitative research, aiming to discover and identify the perception of people with diabetes on the services provided by the public health system. In this sense, the perception of people with diabetes was analysed from the perspective of psycho-social dimensions of diabetes behaviour. The exploratory research was based on the collection of opinions and behavioural knowledge expressed by the respondents. The information obtained was used to define the hypotheses and continued to be tested through quantitative research. The results and conclusions refer to the degree of adaptation of the public health system to the needs and expectations of people with type II diabetes. The results of the research can be used to suggest solutions for adapting the public health system to the needs and expectations of people with diabetes in particular, which can be extended to the general level.
Keywords: public health system; people with diabetes; quantitative research; types of support